Gut, Microbiome, and Brain Regulatory Axis: Relevance to Neurodegenerative and Psychiatric Disorders - Stefano, G B; Pilonis, N; Ptacek, R; Raboch, J; Vnukova, M; Kream, R M (Cellular and molecular neurobiology, 2018)
It has become apparent that the molecular and biochemical integrity of interactive families, genera, and species of human gut microflora is critically linked to maintaining complex metabolic and behavioral processes mediated by peripheral organ systems and central nervous system neuronal groupings. Relatively recent studies have established intrinsic ratios of enterotypes contained within the human microbiome across demographic subpopulations and have empirically linked significant alterations in the expression of bacterial enterotypes with the initiation and persistence of several major metabolic and psychiatric disorders. Accordingly, the goal of our review is to highlight potential thematic/functional linkages of pathophysiological alterations in gut microbiota and bidirectional gut-brain signaling pathways with special emphasis on the potential roles of gut dysbiosis on the pathophysiology of psychiatric illnesses. We provide critical discussion of putative thematic linkages of Parkinson's disease (PD) data sets to similar pathophysiological events as potential causative factors in the development and persistence of diverse psychiatric illnesses. Finally, we include a concise review of preclinical paradigms that involve immunologically-induced GI deficits and dysbiosis of maternal microflora that are functionally linked to impaired neurodevelopmental processes leading to affective behavioral syndromes in the offspring.
Keywords: Gastrointestinal Microbiome; Microbiome; mozek; Humans; FOXG1; mikrobiota; Microbiota; Monoamines; lidé; zvířata; dysbióza; duševní poruchy; Brain; Dysbiosis; Mental Disorders; Psychiatry; Depression; střevní mikroflóra; Animals; Bacteria; Parkinson Disease; Antibiotics; Parkinsonova nemoc